2018
DOI: 10.1364/boe.9.002476
|View full text |Cite
|
Sign up to set email alerts
|

Beyond backscattering: optical neuroimaging by BRAD

Abstract: Optical coherence tomography (OCT) is a powerful technology for rapid volumetric imaging in biomedicine. The bright field imaging approach of conventional OCT systems is based on the detection of directly backscattered light, thereby waiving the wealth of information contained in the angular scattering distribution. Here we demonstrate that the unique features of few-mode fibers (FMF) enable simultaneous bright and dark field (BRAD) imaging for OCT. As backscattered light is picked up by the different modes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The enhancement proposed in this communication could help simplifying OCT applications that essentially rely on a long axial range, such as those mentioned earlier in this communication, [2][3][4][5] or just long axial range imaging applications, such as full corneal imaging. 9 Depending on the application, this might need to be complemented by using either low NA interface optics in the sample arm or by employing Bessel beams.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The enhancement proposed in this communication could help simplifying OCT applications that essentially rely on a long axial range, such as those mentioned earlier in this communication, [2][3][4][5] or just long axial range imaging applications, such as full corneal imaging. 9 Depending on the application, this might need to be complemented by using either low NA interface optics in the sample arm or by employing Bessel beams.…”
Section: Resultsmentioning
confidence: 96%
“…An axial range exceeding meters was demonstrated in a recent report on ultra-long coherence length VCSEL tunable lasers. 1 These long axial range SS-OCT systems are useful in a number of scenarios, ranging from obtaining vascularization maps of large sections of tissue 2, 3 to depth-encoding several measurements in SS-OCT systems with extended functionality, such as passive, multiple input state PS-OCT 4 and the BRAD concept, 5 which allows the sample to be imaged with different orientation angles via a multi-mode optical fiber.…”
Section: Introductionmentioning
confidence: 99%
“…PS-OCT visualizes amyloid-beta plaques based on their optical scattering and birefringent properties [33][34][35][36]. Previous studies mainly exploited the hyperscattering characteristics of plaques and only one report investigated the birefringent characteristics of neuritic plaques using PS-OCT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated that amyloid-beta plaques in both human and mouse brain tissue can be visualized using either conventional OCT, PS-OCT [19,[32][33][34][35][36] or other functional extensions such as spectroscopic OCT [32] or directional OCT [36]. Label-free imaging of cerebral amyloid-beta plaques has been achieved using extended-focus optical coherence microscopy (OCM) in the near infrared range at 800 nm [34].…”
Section: Introductionmentioning
confidence: 99%
“…a/LCI is not the only modality which measures elastic scattering from biological media. Eugui et al have recently suggested the use of few‐mode fibers in optical coherence tomography for angular scattering detection in tissue, severely discretizing the scattering function into three transmitting modes in an optical fiber . Smith et al combined angular elastic scattering with Raman scattering for characterization of human immune cells, with a reduced angular range ( θ r of 19°) as compared with a/LCI .…”
Section: Introductionmentioning
confidence: 99%